Neuromuscular interaction of jaw and neck muscles during jaw clenching - Giannakopoulos, Nikolaos Nikitas; Hellmann, Daniel; Schmitter, Marc; Krüger, Bastian; Hauser, Thomas; Schindler, Hans J. (Journal of orofacial pain, 2013)
AIMS: To test the hypothesis that jaw muscles and specific neck muscles, ie, levator scapulae, trapezius, sternocleidomastoideus, and splenius capitis, co-contract at the different submaximum bite forces usually generated during jaw clenching and tooth grinding, and for different bite force directions. - METHODS: Bite-force transducers that measured all three spatial force components were incorporated in 11 healthy subjects. The test persons developed feedback-controlled submaximum bite forces in a variety of bite-force directions. The electromyographic (EMG) activity of the levator scapulae, splenius capitis, and trapezius muscles was recorded, at the level of the fifth cervical vertebra, by use of intramuscular wire electrodes. The activity of the sternocleidomastoideus and masseter muscles was recorded by surface electrodes. For normalization of the EMG data, maximum-effort tasks of the neck muscles were conducted in eight different loading directions by means of a special force-transducer system. Differences between neck-muscle activity during chewing, maximum biting in intercuspation, and the force-controlled motor tasks were compared with the baseline activity of the various muscles by one-way repeated-measures analysis of variance. - RESULTS: The results confirmed the hypothesis. Co-contractions of the neck muscles in the range of 3% to 10% of maximum voluntary contraction were observed. Significant (P < .05) activity differences were recorded as a result of the different force levels and force directions exerted by the jaw muscles. Long-lasting action potential trains of single motor units triggered by jaw clenching tasks were also detected. - CONCLUSION: The findings support the assumption of a relationship between jaw clenching and the neck muscle activity investigated. The low level of co-contraction activity, however, requires further study to elucidate possible pathophysiological interactions at the level of single motor units.
Gesehen am 11.03.2021